Vaccines Against Shigella and Enterotoxigenic Escherichia coli: A summary of the 2018 VASE Conference. Issue 34 (7th August 2019) - Barry, Eileen; Cassels, Fred; Riddle, Mark; Walker, Richard; Wierzba, Thomas
Abstract: PATH hosted the second Vaccines Against Shigella and Enterotoxigenic Escherichia coli (VASE) Conference in Mexico City in June 2018, again providing experts from around the world an opportunity to participate in a highly collaborative forum to discuss progress in the development of new enteric vaccines. Through a combination of plenary sessions and posters, keynote presentations, and workshops, the 2018 VASE Conference aimed to accelerate communication and progress among those working to achieve the goal of licensed vaccines against these two bacterial pathogens. Many presentations recognized the importance of diarrheal disease and long-term sequelae caused by infections with Shigella and enterotoxigenic E. coli (ETEC). Other presentations explored new strategies for vaccine development, including the search for novel, possibly conserved, antigens for more effective vaccines. Much progress is being made as some vaccine candidates are now moving through clinical trials. Research presented in oral and poster presentations at the VASE Conference covered a range of topics, including: the global burden of disease, epidemiology, and health economics; host parameters and genomics that predict responses to infection and disease; preclinical evaluations of vaccine antigens and models of enteric diseases; and vaccine candidates in clinical trials and human challenge studies. This article reviews key points and highlighted research presented in each of the plenary conference sessions and poster presentations at the 2018 VASE Conference.